Foraging Activity of Native Ants on Trees in Forest Fragments Colonized by the Invasive Ant Lasius neglectus. (18th June 2012) - Paris, C.; Espadaler, X.
Abstract : Our aim was to investigate the foraging activity of native ants on tree trunks in accordance with their location in forest fragments and the presence or absence of the invasive ant Lasius neglectus . Trees were categorized as isolated, edge, or core trees according to their location in forest fragments. In invaded fragments, Lasius neglectus had the highest spatial-temporal tree visitation. Isolated trees were visited more and for a longer time by this invasive ant. Invaded fragments had low native ant activity on trees compared to fragments without L. neglectus . The few encountered native ant species showed a lower frequency of visitation and for less time in comparison with their spatial-temporal visitation in control fragments. Crematogaster scutellaris and Temnothorax lichtensteini visited all tree categories in both fragments (invaded or control) but Lasius grandis stayed for longer on isolated trees from control fragments. We conclude that in fragments invaded by Lasius neglectus, the richness of native ant foraging on trees was negatively affected. Isolated trees close to roads could act as dispersal stepping stones for Lasius neglectus .